1984
DOI: 10.3109/02713688408997230
|View full text |Cite
|
Sign up to set email alerts
|

The optical effects of eyelid closure on the eyes of kittens reared in light and dark

Abstract: Monocular closure surgically performed during development by suturing the eyelids induced less hyperopia in the closed eye of light reared kittens (+0.95 Diopters) in comparison to the closed eyes of lid sutured dark reared kittens (+2.61 D). The normal control cats were also slightly hypermetropic (+0.69 D). While a certain proportion of myopic eyes was found in the monocularly closed light reared kittens and in the normal control cats, no one eye was myopic either in the operated or nonoperated dark reared k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…For example, Mutti et al (2005) reported that in young infants 3 to 9 months of age, the reduction in hyperopia associated with emmetropization correlated primarily with axial elongation with little contribution from either the lens or cornea, although both the lens and cornea are growing and losing optical power during this period. Moreover, for anisometropic subjects, refractive-error studies of humans (Logan et al, 2004) and many animals, (e.g., chicken (Hodos et al, 1985; Hodos & Kuenzel, 1984; Wallman et al, 1978; Yinon et al, 1980), tree shrews (Marsh-Tootle & Norton, 1989; Sherman et al, 1977), marmosets (Troilo & Judge, 1993), cats (Gollender et al, 1979; Kirby et al, 1982; Yinon et al, 1984), pigeons (Bagnoli et al, 1985), grey squirrels (McBrien et al, 1993), the American kestrel (Andison et al, 1992), barn owls (Knudsen, 1989), guinea pigs (Howlett & McFadden, 2006), wallabies (Harman et al, 1999), rabbits (Gao et al, 2006) and mice (Tejedor & de la Villa, 2003)) have all reported significant interocular differences in vitreous chamber depth in anisometropic individuals. Nonetheless, the ages of the monkeys used in this study were equivalent to about 1–2 years of age for human infants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mutti et al (2005) reported that in young infants 3 to 9 months of age, the reduction in hyperopia associated with emmetropization correlated primarily with axial elongation with little contribution from either the lens or cornea, although both the lens and cornea are growing and losing optical power during this period. Moreover, for anisometropic subjects, refractive-error studies of humans (Logan et al, 2004) and many animals, (e.g., chicken (Hodos et al, 1985; Hodos & Kuenzel, 1984; Wallman et al, 1978; Yinon et al, 1980), tree shrews (Marsh-Tootle & Norton, 1989; Sherman et al, 1977), marmosets (Troilo & Judge, 1993), cats (Gollender et al, 1979; Kirby et al, 1982; Yinon et al, 1984), pigeons (Bagnoli et al, 1985), grey squirrels (McBrien et al, 1993), the American kestrel (Andison et al, 1992), barn owls (Knudsen, 1989), guinea pigs (Howlett & McFadden, 2006), wallabies (Harman et al, 1999), rabbits (Gao et al, 2006) and mice (Tejedor & de la Villa, 2003)) have all reported significant interocular differences in vitreous chamber depth in anisometropic individuals. Nonetheless, the ages of the monkeys used in this study were equivalent to about 1–2 years of age for human infants.…”
Section: Discussionmentioning
confidence: 99%
“…First, whereas form deprivation induces myopia reliably in many species including primates (Daw, 2006), the outcome for cats is inconsistent and far less marked. At one extreme, two studies report that image degradation, even when prolonged, does not produce myopia at all in kittens (Nathan, Crewther, Crewther, & Kiely, 1984;Smith, 1981), while other studies report either only mild myopia in a very small proportion (17.6%) of animals (Yinon, Koslowe, & Rassin, 1984) or else non-systematic changes (Gollender, Thorn, & Erickson, 1979). Even when myopia was reported reliably (Smith, Maguire, & Watson, 1980;Wilson & Sherman, 1977), its magnitude was small and much less than that observed in monkeys.…”
Section: The Possible Impact Of Form Deprivation Myopia (Fdm)mentioning
confidence: 96%
“…Coppola and L.E. While it is known that dark-rearing effects eye development-leading to mild hypermetropia in most casesthere are no data to suggest that dark-rearing causes the extreme and rare form of astigmatism that would be necessary to explain a vertical bias in cortical orientation preference (see also Yinon et al, 1984;Guyton et al, 1989;Kee et al, 2002). Another possible explanation for the transient cardinal bias in normal juvenile ferrets is that this bias is attributable to a corneal astigmatism that disappears as the eye grows to its adult shape.…”
Section: Orientation Anisotropy In Dark-reared and Normal Ferretsmentioning
confidence: 99%